Retranslating number expression unknown word in Chinese-Vietnamese statistical machine translation - Trần, Phước Thanh; Đinh, Điền (Journal of Computer Science and Cybernetics, 2014)
<!–[if gte mso 9]> <![endif]–> Word boundary in Chinese and Vietnamese is not defined by a space. Therefore, Chinese-Vietnamese word segmentations are always done first in Chinese-Vietnamese natural language processing problem in general and in Chinese-Vietnamese statistical machine translation in particular. The word segmentation increases the final quality of translation, but it appears many unknown words (UKW) in the target translation. The type of popular unknown word in Chinese-Vietnamese translation system is named entity (NE). In this paper, we present a hybrid method to combine statistic and rule and to re-translate number expression NE-UKW (NumExp-NE-UKW). Applying this method into Chinese-Vietnamese SMT, the experiment result shows that our method significantly improves Chinese-Vietnamese SMT performance. <!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –>